2022
DOI: 10.1093/procel/pwac037
|View full text |Cite
|
Sign up to set email alerts
|

4E-BP1 counteracts human mesenchymal stem cell senescence via maintaining mitochondrial homeostasis

Abstract: Although the mTOR-4E-BP1 signaling pathway is implicated in aging and aging-related disorders, the role of 4E-BP1 in regulating human stem cell homeostasis remains largely unknown. Here, we report that the expression of 4E-BP1 decreases along with the senescence of human mesenchymal stem cells (hMSCs). Genetic inactivation of 4E-BP1 in hMSCs compromises mitochondrial respiration, increases mitochondrial reactive oxygen species (ROS) production, and accelerates cellular senescence. Mechanistically, the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Mitochondrial dysfunction, characterized by swollen mitochondria, fragmentation of the mitochondrial network, and imbalance of mitochondrial functions, is a hallmark of aging [ 18 , 57 – 59 ]. This phenomenon has been observed in aged flies, worms, and human stem cells [ 16 , 45 , 60 64 ]. Our study revealed that MAVS depletion impaired mitochondrial dynamics and homeostasis, as reflected by abnormal mitochondrial morphology and compromised mitochondrial functions.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Mitochondrial dysfunction, characterized by swollen mitochondria, fragmentation of the mitochondrial network, and imbalance of mitochondrial functions, is a hallmark of aging [ 18 , 57 – 59 ]. This phenomenon has been observed in aged flies, worms, and human stem cells [ 16 , 45 , 60 64 ]. Our study revealed that MAVS depletion impaired mitochondrial dynamics and homeostasis, as reflected by abnormal mitochondrial morphology and compromised mitochondrial functions.…”
Section: Discussionmentioning
confidence: 76%
“…Co-IP assays were performed following previous studies [ 16 , 45 ]. MAVS-interacting proteins were identified through Co-IP using plasmids expressing Flag-Luc or Flag-MAVS transfected into HEK293T cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary hMSCs were isolated from a 76‐year‐old healthy male gingiva tissues according to previous report (Hu et al , 2020; He et al , 2022). Briefly, the gingiva tissues were cut into granule and digested in TrypLE (Thermo Fisher Scientific) and Dispase IV (Thermo Fisher Scientific) at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described. 25,26 Tissues or cells were lysed with SDS lysis buffer containing 2% SDS and 62.5 mM Tris-HCl (pH = 6.8) and incubated at 100 C for 10 min.…”
Section: Western Blot Analysismentioning
confidence: 99%